VAARTALAP: Embedding Whisper-AI-like Model into a Video-Conferencing System to Aid Real-Time Translation and Transcription - Kashyap, Kunal; Singh, Prashant; Verma, Anjali; Mishra, Satya; Goel, Prachi (International Journal of Computer Sciences and Engineering, 2023)
In this world of digitalized communication, effective communication crosses regional boundaries and linguistic obstacles making the world more connected. The demand for seamless multilingual communication has never been more important as corporations, institutions, and individuals engage on a worldwide scale. This article explores a trailblazing initiative that uses real-time translation and transcription services offered by Whisper-AI to transform the world of video conferences. The goal of the research is to create an AI model that easily interfaces a translation and transcription-based model to work in a real-time video conferencing system. Participants may converse in real-time without any language barriers by utilizing cutting-edge voice recognition and translation technologies.